PATIENTS PERCEPTIONS ON VERBAL COMUNICATION OF TEAM NURSING - Liliana M. Labronici; Ricardo Debastiani Viana; Verônica de Azevedo Mazza; Maguida Costa Stefanelli (Universidade Federal do Paraná, 1998)
Descriptive study which purpose is to know how the patient/client perceives the communication that happens in the nursing process. Interviews have been performed with patients from specialized Clinicai Units of the hospital where this research have been developed. The analysis of their contents allows the extraction of the following categories: "make", "doesn't make", "technical speech", "social speech", "a short speech". These categories reveal that when the nurse-patient communication happens, it takes place in nursing actions, on a verbal and a non verbal manner, but in a inadequate manner, because it doesn't reflect nursing interpersonal competence in communication. The patient is not allowed to express what he is experiencing, thinking or feeling about it. It is necessary that the nursing team be oriented and prepared about the importance of the association of the conscious use of the adequate OR therapeutic communication in his nursing practice, as a way of living.